Chronic Skull Base Erosion from Temporomandibular Joint Disease Causes Generalized Seizure and Profound Lactic Acidosis. (27th September 2018) - Dobish, Mark A.; Wyler, David A.; Farrell, Christopher J.; Dhami, Hermandeep S.; Romo, Victor M.; Choi, Daniel D.; Reed, Travis; Mahla, Michael E.
Abstract : This report displays a rare presentation of lactic acidosis in the setting of status epilepticus (SE). The differential diagnosis of lactic acidosis is broad and typically originates from states of shock; however, this report highlights an alternative and rare etiology, SE, due to chronic skull base erosion from temporomandibular joint (TMJ) disease. Lactic acidosis is defined by a pH below 7.35 in the setting of lactate values greater than 5 mmol/L. Two broad classifications of lactic acidosis exist: a type A lactic acidosis which stems from global or localized tissue hypoxia or a type B lactic acidosis which occurs once mitochondrial oxidative capacity is unable to match glucose metabolism. SE is an example of a type A lactic acidosis in which oxygen delivery is unable to meet increased cellular energy requirements. This report is consistent with a prior case series that consists of five patients experiencing generalized tonic-clonic (GTC) seizures and lactic acidosis. These patients presented with a pH range of 6.8-7.41 and lactate range of 3.8-22.4 mmol/L. Although severe lactic acidosis following GTC has been described, this is the first report in the literature of chronic skull base erosion from TMJ disease causing SE.